Detection of Porcine DNA in Processed Beef Products Using Real Time - Polymerase Chain Reaction - Septiani, Triayu (UIN Sunan Gunung Djati Bandung, 2019)
Meat is one of food materials which has protein source and mostlyconsumed by non-vegetarian. Consuming halal food is an obligation for every Muslim. Meat processed products usually contaminated by pork. One of technique that is often chosen as an authentication process for proofing halalness of the product is PCR technique, one of PCR technique which most commonly used is RT-PCR. RT-PCR technique was chosen as identification method because it has high accuration for detection of porcine DNA in fresh meat and processed products. RT-PCR is the amplification technique in the specific regions that are restricted by two oligonucleotide with the help of polymerase enzymes. Annealing is the first process of RT-PCR analysis who was primary attachment to the DNA template that determines the specificity and amount of DNA produced. In this study, extraction kit and detection kit were used for analysis Porcine DNA in meatballs. The results obtained from this study were from whole DNA samples, which had DNA purity ranging from 1.82 to 1.93. From the all samples three of them containing porcine DNA. The positive samples shown from amplification curves who was specifically formed when probes reacts with porcine gene.